Porous and single-crystalline ZnO nanobelts: fabrication with annealing precursor nanobelts, and gas-sensing and optoelectronic performance. (25th July 2016) - Jin, Xiao-Bo; Li, Yi-Xiang; Su, Yao; Guo, Zheng; Gu, Cui-Ping; Huang, Jia-Rui; Meng, Fan-Li; Huang, Xing-Jiu; Li, Min-Qiang; Liu, Jin-Huai
Abstract: Porous and single-crystalline ZnO nanobelts have been prepared through annealing precursors of ZnSe · 0.5N2 H4 well-defined and smooth nanobelts, which have been synthesized via a simple hydrothermal method. The composition and morphology evolutions with the calcination temperatures have been investigated in detail for as-prepared precursor nanobelts, suggesting that they can be easily transformed into ZnO nanobelts by preserving their initial morphology via calcination in air. In contrast, the obtained ZnO nanobelts are densely porous, owing to the thermal decomposition and oxidization of the precursor nanobelts. More importantly, the achieved porous ZnO nanobelts are single-crystalline, different from previously reported ones. Motivated by the intrinsic properties of the porous structure and good electronic transporting ability of single crystals, their gas-sensing performance has been further explored. It is demonstrated that porous ZnO single-crystalline nanobelts exhibit high response and repeatability toward volatile organic compounds, such as ethanol and acetone, with a short response/recovery time. Furthermore, their optoelectronic behaviors indicate that they can be promisingly employed to fabricate photoelectrochemical sensors.